The Quality of Water of the Weija Dam and the Densu River - Nee-Whang, G. (University of Ghana, 1999)
In recent years there has been an immense public outcry over the concern of the quality of water from the Densu River and the Weija reservoir. In an attempt to study the quality of water from the Densu River and the Weija reservoir, a 2 x 5 factorial experiment with two seasons (rainy and dry) and five sources of water (Akwadum, Asuboi, Nsawam, Manhia and the Weija Dam) as variables was performed. These water samples were analysed for various physical, chemical, nutritive and microbiological indices of water quality using the American Public Health Association (APHA) Standard Methods. As well, the quality of water from the surface and bottom levels of the Weija Dam were analysed and compared with that of treated water from the Weija Dam. The results of the quality of water from this current studies were compared to the quality of water from the Densu River Basin at the pre-impoundment era. The quality status of water from the Densu River and the Weija reservoir revealed that generally the water can be classified as an acceptable source of water supply even though it is quite polluted. This is because the present quality is comparable to that of the pre-impoundment era, which was classified as a good source of water supply using Todd’s classification of water quality on the Densu River. Contrary to this classification, phosphate level of the Densu River at that time was as high as that of the highly eutrophic Lake Barekese in the Ashanti Region, which ranged from 0.01-1.2 mg/L. However, predictions from earlier studies stated that if the phosphate levels observed at that time was maintained, the Weija Lake would suffer from eutrophication and its attendants problems, which includes poor quality and high cost of treatment. With a range of 0.08-0.64 mg/L, this study reveals that the current quality status of water in Densu River Basin confirms the prediction. Nutritively, the high phosphate level coupled with the dramatic increase in BOD levels that have no guideline values, and ranged from 0.77-9.9 mg/L during the period under consideration is indicative of the level of organic matter pollution. In addition, the low Dissolved Oxygen (DO) levels, which range from 1.6-9.4 mg/L indicates poor nutritive quality. Physically, the quality of water in the Densu River basin can be said to be poor as suggested by the high colour value (30-90 TCU against a guideline value of 15 TCU), turbidity (6-54 NTU against a guideline value of 5 NTU), pH (7.5-8.4) and conductivity (162-681 |xg/cm as against a guideline value of 400 ng/cm). Biologically, the chlorophyll A levels ranging from 16.5 - 83.0 |ig/cm, which even though were not excessive, indicates a degree of algal biomass. Total coliform (TC) and faecal coliform (FC) counts, which ranged from 100-1940 count/100ml are indicative of high microbial contamination, reflecting poor sanitary conditions in the Basin. Chemically, the quality of water in the basin can be said to be acceptable except for Iron which had values ranging between 0.2-1.59 mg/L, which was above the guideline value 0.3 mg/L, and chloride that had values within 9.2 and 112.0 mg/L, is indicative of some level of pollution. The comparative studies between the quality of water in the rainy and dry seasons revealed that generally the quality of water in the Densu River Basin is better in the rainy season than the dry season. Trends in the water quality were also observed to decrease down across the Densu River Basin. However, water from the Weija dam was relatively better in quality compared to the quality of water in the Densu River Basin. In conclusion, the quality of water from both the Densu river and the Weija Dam were regarded acceptable and within the guideline values given for their physical, chemical and microbiological quality limits, even though a few chemical indices showed values that were slightly above their guideline limits. This signifies water from both the Weija Dam and the Densu River Basin are polluted. However, the level of pollution observed in the two water bodies though quite high, is not high enough to conclude that they are bad sources of water for human activities and treatment for consumption. The study therefore recommends among others, the improvement of the quality in the management process of water in the Densu River Basin. These may involve the enforcement of regulations regarding fishing and farming in the Densu River Basin, improvement of sanitary conditions, education as well as follow-up research studies to be conducted on the quality o f water from the basin.
Thesis (MPhil) -University of Ghana, 1999